KARAKTERISTIK SEBARAN PERGERAKAN MENGGUNAKAN METODE SINTETIS GRAVITY KECAMATAN SAMARINDA ULU - TAUFIK RAHMAN (KURVA MAHASISWA, 2018)
Movements or moves are displacements from the original zone to the destination zone using either private modes or general modes at close or long distances. The journey is a routine that every day people do. The need for travel always creates transportation problems, especially when humans travel at the TeSamarinda city with a population of 126,660 people with an area of 58.26 km². The purpose of this study is to determine the characteristics and patterns of travel travel distribution in subdistrict samarinda ulu.This research use interview method, data used in the form of secondary data that is population of Sub Samarinda Ulu and primary data that is from result of interview to vehicle user in random and insedental penenlitian area. Data analysis method used is the synthetic gravity method which is poured in two dimensional matrix which is often called the matrix of origin of destination (MAT).Identify the characteristics of the spread of travel motion obtained by the result of 40.284% of the largest movement with the purpose of traveling school and 59.336% of the largest movement using a motorcycle vehicle. Analysis of the spread of travel movement generated the pattern of distribution of movement with the origin of the greatest movement is found in Kelua Kelurahan by 18% and the largest goal of moving to Kelua Kelurahan by 20%. The research conducted at Samarinda Ulu Sub-district was obtained by the biggest movement of Kelua Gunung Kelua, the largest movement to Kelua Gunung Kelua Village with the purpose of school movement movement using motorcycle